Saturasi Oksigen Pada Petugas Di Terminal Yang Terpapar Karbon Monoksida Udara - Katerina Kanthi Rosari; Junaidi Junaidi; Zulfikar Ali As (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2020)
Monoxide (CO) bonds with blood are 200 times stronger than oxygen bonds with blood. When inhaled CO will be absorbed through the lungs following the blood circulation and binds to haemoglobin to form HbCO in the tissues which will block the entry of oxygen needed by the body. The purpose of this study was to determine the relationship of air CO levels with oxygen saturation (SpO2) in officers in Terminal Type B of South Kalimantan Province. This type of research is analytically using a cross-sectional design with a sample of 24 people. Data collection was carried out by interview, observation, CO measurement and SpO2 examination with Pulse Oximetry. The results showed that there was a relationship between air CO levels and the SpO2 of terminal officers with a significance value of 0.0025 (sig.